ANALYSIS OF THE RELATIONSHIP BETWEEN THE ABILITY TO IDENTIFY MAIN IDEAS OF AURAL TEXTS AND INDONESIAN LANGUAGE LEARNING OUTCOMES - Naofalia, Salwa (Asosiasi dosen IDEBAHASA KEPRI, 2025)
Listening skills, particularly the ability to identify main ideas in aural texts, constitute an important foundation in Indonesian Language learning at elementary schools, yet their relationship with student learning outcomes has not been extensively explored empirically. This study aimed to analyze the relationship between the ability to identify main ideas in aural texts and Indonesian Language learning outcomes among fourth-grade elementary school students. The study employed a quantitative correlational approach involving 30 fourth-grade students. Data were collected through multiple-choice written tests to measure the ability to identify main ideas in aural texts and documentation of final semester summative scores. Data analysis used the Spearman Rank correlation test due to non-normal data distribution. The results showed that students' ability to identify main ideas in aural texts was in the good category with an average of 83.27, as well as Indonesian Language learning outcomes with an average of 83.633. There was a significant positive relationship with moderate strength between the ability to identify main ideas in aural texts and Indonesian Language learning outcomes (rs = 0.523; p = 0.003). The contribution of the main idea identification ability variable to learning outcomes was 27.35 percent. The research implies the importance of developing systematic listening learning strategies to improve overall Indonesian Language learning outcomes